Taalkundige Essays : N Gerf Uit Die Vroegskemer. - Hendricks, Frank (African Sun Media, 2017)
"This work is a combination of original (new) research, the reworking of earlier published work, as well as the processing of lectures and papers. The contributions in the volume contribute to investigating unexplored areas and refining others in the light of new insights." - Prof. Wannie Carstens, North West University